Prevalence of Nasal Carriage of Staphylococcus aureus among Medical and Veterinary Students (IAHS Medical Journal, 2025)
Background: Nasal carriage among hospital personnel is one of the important sources of staphylococci for causing nosocomial infection. The aim of the study was to determine the nasal carriage rate of S. aureus among medical and veterinary students.Materials and methods: A cross-sectional study was conducted on 81 were medical students and 76 veterinary students. Presumptive S. aureus was identified from nasal swab following conventional bacteriological methods and was confirmed by detecting the presence of species-specific nuc gene by PCR. All staphylococci isolates were tested for antimicrobial susceptibility. Isolates displaying resistance to oxacillin and cefoxitin were further tested for the presence of mecA gene by PCR.Results: About 80% of the total S. aureus isolates from medical students showed Multi-Drug Resistance (MDR) whereas about 50% of the total S. aureus from veterinary students were MDR. Among the 39 isolates obtained from medical students, 20 (51.3 %) were methicillin resistant and the rate of methicillin resistance among veterinary students was 22.2%. Only one factor presence of “Rhinorrhea” was found significantly associated with carriage of Staphylococcus sp. among medical and veterinary students.Conclusion: Nasal carriage of is common and there is high level of resistance against Ampicillin, Penicillin, Ciprofloxacin and Erythromycin.IAHS Medical Journal Vol 7(2), December 2024; 73-77